Penggunaan Media Permainan MOLEGI (Monopoli Kesehatan Gigi) Dalam Meningkatkan Pengetahuan Cara Menyikat Gigi Yang Baik Dan Benar di UPT SPF SD Inpres Baddokka Kecamatan Biringkanaya Kota Makassar - Magfirah, Febi; Eni, St.Nur; AR, Aisyah; Feblina, Ayu Rahayu; Asrini, Una; Zelvanisa, Marsila (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Elementary school students are one of the groups that are vulnerable to dental and oral diseases, especially dental caries because in general students still have less knowledge and behavior to improve the quality of their dental and oral health. Brushing teeth properly is an important factor in maintaining dental and oral health. The success of maintaining dental and oral health is also influenced by the pattern of brushing teeth. One effective way to improve students' knowledge and behavior about health is to use the molegi game (Monopoly of Dental Health) to promote health in schools. The purpose of community service is to measure the level of knowledge of how to brush teeth properly in children. The type of research used in this community service is a pre-experiment with a one group pre-test post-test design, namely an experimental study without a control group, in other words there is only one group that will fill out the questionnaire before and after counseling to 28 4th grade elementary school students using molegi media. When the pre-test evaluation was carried out regarding the material to be presented, it was seen that the level of understanding and knowledge of students at the UPT SPF SD Inpres Baddoka before the counseling was in the sufficient category of 19 people (67.8%) and the good category of 9 people (32.2%). The level of student knowledge after counseling is generally the same as before counseling. However, looking at the percentage of students' knowledge level, the sufficient category decreased from 19 people (67.8%) to 8 people (28.6%) and the good category increased from 9 people (32.2%) before counseling and increased to 20 people (71.4%) after counseling activities. It can be concluded that there is an increase in knowledge after being given counseling using molegi media.